Synthesis, Physicochemical Characterization, Biological Evaluation, In Silico and Molecular Docking Studies of Pd(II) Complexes with P, S-Donor Ligands - Hizbullah Khan; Muhammad Sirajuddin; Amin Badshah; Sajjad Ahmad; Muhammad Bilal; Syed Muhammad Salman; Ian S. Butler; Tanveer A. Wani; Seema Zargar (MDPI AG, 2023)
One homoleptic (1) and three heteroleptic (2-4) palladium(II) complexes were synthesized and characterized by various physicochemical techniques, i.e., elemental analysis, FTIR, Raman spectroscopy, 1H, 13C, and 31P NMR. Compound 1 was also confirmed by single crystal XRD, showing a slightly distorted square planar geometry. The antibacterial results obtained via the agar-well diffusion method for compound 1 were maximum among the screen compounds. All the compounds have shown good to significant antibacterial results against the tested bacterial strains, Escherichia coli, Klebsiella pneumonia, and Staphylococcus aureus, except 2 against Klebsiella pneumonia. Similarly, the molecular docking study of compound 3 has shown the best affinity with binding energy scores of −8.6569, −6.5716, and −7.6966 kcal/mol against Escherichia coli, Klebsiella pneumonia, and Staphylococcus aureus, respectively. Compound 2 has exhibited the highest activity (3.67 µM), followed by compound 3 (4.57 µM), 1 (6.94 µM), and 4 (21.7 µM) against the DU145 human prostate cancer cell line using the sulforhodamine B (SRB) method as compared to cisplatin (>200 µM). The highest docking score was obtained for compounds 2 (−7.5148 kcal/mol) and 3 (−7.0343 kcal/mol). Compound 2 shows that the Cl atom of the compound acts as a chain side acceptor for the DR5 receptor residue Asp B218 and the pyridine ring is involved in interaction with the Tyr A50 residue via arene-H, while Compound 3 interacts with the Asp B218 residue via the Cl atom. The physicochemical parameters determined by the SwissADME webserver revealed that no blood-brain barrier (BBB) permeation is predicted for all four compounds, while gastrointestinal absorption is low for compound 1 and high for the rest of the compounds (2-4). As concluding remarks based on the obtained in vitro biological results, the evaluated compounds after in vivo studies might be a good choice for future antibiotics and anticancer agents.